(untitled) - Alan Duff (London, 1996)
This book is designed specifically with the needs of the foreign language learner in mind. No previous knowledge of literature is needed either by the teacher or by the students, since it is not a book about how to study literature, but on how to use it for language practice
Keywords: english language - study and teaching